Pemanfaatan Lingkungan Sekitar sebagai Media Pembelajaran pada Mata Pelajaran IPS untuk Meningkatkan Hasil Belajar Peserta Didik di MI Darus Sa’adah Jekulo Kudus - Nofrita Nofrita (ILUMINASI: Journal of Research in Education, 2023)
This research is a Classroom Action Research (PTK) which consists of three cycles. The problem in this study is the low teaching method used at MI Darus Sa'adah Jekulo Kudus. Therefore researchers seek to increase the activity and learning outcomes of students by using the surrounding environment as a learning medium. The use of the surrounding environment as social studies learning media to improve student learning outcomes in class V MI Darus Sa'adah Jekulo Kudus has increased from cycles I, II and III by looking at percentages. The data after implementing the use of the surrounding environment as a learning medium always shows a significant increase. This means that social studies learning completeness by applying the use of the surrounding environment in cycle I, cycle II and cycle III has always increased and has reached the researcher's target of 85%.